Jaringan Purnawirawan Tentara Nasional Indonesia dalam Politik Relasi Sipil–Militer Pasca Reformasi TNI - Soesilo, Arie S. (Masyarakat: Jurnal Sosiologi, 2014)
This article discusses the entering process of retired military (TNI) officers into politics and their performances in that arena. This article argues that the retired military officer’s roles in politics provided new characteristics to the pattern of civil-military relations in Indonesia. It related to their capability to bridge the communication and to act as muting agent in political conflict between civil and military politicians. This article also asserts that the involvement of retired military officers in politics is strongly based on their commitment to the constitution in building democratic consolidation, which is not representing military interests. Thereby, it criticizes existing studies stated that the involvement of retired military officers in politics is part of the military institution’s attempts to capture the state power through democratic mechanism, namely, re-militarization. The approach used by this study is Actor Network Theory (ANT), which is based on performative relation amongst actors (actants), both human and nonhuman actants. This approach was used to generate a detailed explanation of certain event through an inquiry of relational process amongst actors within network.